The assessment of dementia severity using non-verbal cognitive tests - Khan, Sobia T. (2010)
Objective: To explore the utility of cognitive tests, that did not rely on spoken language from participants for decision making about eligibility for treatment with Anti-cholinesterase Inhibitors (AchI).